Implementation of Principal Academic Supervision in Improving Teacher Performance at Schools Mis Hubbul Wathon Sei Berombang - Filma Muhazri Sembiring; Alfieridho Alfieridho; Cendani Alfanizha Hidma; Indah Wahyuni; Arina Denggan Munthe; Renilda Putri (Universitas Muhammadiyah Enrekang, 2022)
Academic supervision has the aim of influencing the development and management of the learning process in schools for the better. The purpose of this research is to complement teacher administration, discipline, commitment, and implementation barriers to supervision to manage the learning process. This research is qualitative, namely by using observation and interview techniques for data collection. With the results we can conclude that the supervisory research at MIS HUBBUL WATHON SEI BEROMBANG has followed the management functions to facilitate development in managing the learning process in improving the quality of teacher work.